2022
DOI: 10.31635/ccschem.021.202101286
|View full text |Cite
|
Sign up to set email alerts
|

Whither Second-Sphere Coordination?

Abstract: The properties of coordination complexes are dictated by both the metals and the ligands. The use of molecular receptors as second-sphere ligands enables significant modulation of the chemical and physical properties of coordination complexes. In this Mini-Review, we highlight recent advances in functional systems based on molecular receptors as second-sphere coordination ligands, as applied in molecular recognition, synthesis of mechanically interlocked molecules, separation of metals, catalysis, and biomolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 148 publications
(192 reference statements)
0
20
0
Order By: Relevance
“…36,38,39 For instance, literature studies have demonstrated that smallmolecule catalysis, such as the reduction of CO 2 , O 2 , H + , and oxidation of NH 3 and H 2 O, could benefit rationally by finetuning the secondary coordination sphere of the corresponding catalysts. [40][41][42][43][44][45][46] The manipulation of the secondary coordination sphere of Ru-based WOCs has primarily been achieved via non-covalent interactions, such as hydrogen bonding, π-π stacking, hydrophobic/hydrophilic effects, steric hindrance, and electronic influence. 38,39 Although various approaches have been employed to control the primary and secondary coordination spheres of Ru catalysts toward the WOR, 47 there is minimal information on the cross-comparison of these studies from the kinetic and thermodynamic points of view.…”
Section: Introductionmentioning
confidence: 99%
“…36,38,39 For instance, literature studies have demonstrated that smallmolecule catalysis, such as the reduction of CO 2 , O 2 , H + , and oxidation of NH 3 and H 2 O, could benefit rationally by finetuning the secondary coordination sphere of the corresponding catalysts. [40][41][42][43][44][45][46] The manipulation of the secondary coordination sphere of Ru-based WOCs has primarily been achieved via non-covalent interactions, such as hydrogen bonding, π-π stacking, hydrophobic/hydrophilic effects, steric hindrance, and electronic influence. 38,39 Although various approaches have been employed to control the primary and secondary coordination spheres of Ru catalysts toward the WOR, 47 there is minimal information on the cross-comparison of these studies from the kinetic and thermodynamic points of view.…”
Section: Introductionmentioning
confidence: 99%
“…The sensing functions of high sensitivity, high selectivity and low systematic error can be achieved by lanthanide MOFs with two emission centers because of their excellent self-calibration function and color gradient feature originated from the multi-emission centers 26 31 . To achieve high-performance recognition for UV-vissilent TMAO, a well-matched host-guest interaction between the inner and outer coordination sphere in lanthanide MOFs is essential 32 . Since TMAO is an electron donor, the functionalization of lanthanide MOFs by an electron acceptor is a rational approach, but it has not been realized in MOF chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Noncovalent bonding interactions lay the foundation for almost all the communications between molecules in chemical and biological systems, such as molecular recognition, self-assembly, signal transduction, , and catalysis. Understanding these interactions not only can offer keys to mimicking , the structural and functional aspects of living systems, but also can enrich the toolkit for advanced noncovalent syntheses. Whereas the dynamic nature of noncovalent bonding interactions is beneficial for the construction of smart materials with responsiveness and adaptivity, a large proportion of these interactions are weak, labile, and sometimes transient, making it difficult to characterize and investigate them in depth. Particularly when it comes to complicated supramolecular systems involving multiple interactions, the contribution of weak interactions tends to be obscured by stronger ones.…”
Section: Introductionmentioning
confidence: 99%